Chemasia Engineering Sdn. Bhd. - Ooi, Chooi Lee (1998)

(untitled)
Mr. Chen Yew Seong 75 years old, is facing one of the most remarkable decision of h is career profession. His ambition to public listed the company ChemAsia Engineering Sdn. Bhd. (CAE) a water treatment company, was shake n when Krofta offer to buy 75% of the company's share accounting to USD900,000. Mr. Chen targeted high sales turnover in the near future by using government projected growth rate which is 8%, but deep in his heart it is not realistic. On top of that, he is facing financial problem to support h is water treatment projects. Strategic audit was carried out for CAE, it analyze the company current situation that included performance and strategic posture, external and internal environment scanning by using S.W.O.T. Study on international strategic alliances includes benefits, pitfalls, scope, and the management of alliances. Several alternatives h as been proposed and selection criteria a re used to judge the appropriate solution. The recommended strategy was to sell 49% of CAE share to Krofta. This option enable CAE to solve it's problem while it remain the authority power in the